Ta’bīd al-waqf wa ta’qītuhu fī wilāyāt mukhtārah fī Malaysia - Muhamad Firdaus Ab. Rahman; Muhammad Amanullah (Studia Islamika, 2016)
Muslim jurists differ in the declaration (ṣīghah) of waqf, specifically on whether an endowment can be temporary or it must be in perpetuity. In Malaysia most of the states impose waqf solely on perpetuity property based on the Shafi’i school of jurisprudence. The objective of this paper is to research whether temporary endowments have been enacted and applied in selected states in Malaysia, namely Selangor, Negeri Sembilan, Malacca and Johor. A qualitative methodology was used to analyze the data through inductive, deductive and comparative methods. The research shows that Johor is the only state of Malaysia that has allowed the application of temporary endowments, as stated in section 17 of the Rules of Waqf Johor 1983. It can be implied that fatwas which were issued by the Fatwa Committee regarding Endowments are required to be reassessed from time to time and not limited to the view of a single school of jurisprudence, especially in the field of waqf, without considering the best interests (maṣlaḥah) of contemporary society.DOI: 10.15408/sdi.v23i3.3592